MEKANISME PEMBIAYAAN KREDIT PEMILIKAN RUMAH SYARIAH BAGI MASYARAKAT BERPENGHASILAN RENDAH PADA PT BANK BRI SYARIAH CABANG KAPTEN A RIVAI PALEMBANG - Despa Leni; Serli Anggraini; Muharir Muharir (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
The term financing in the concept is born from the meaning of I believe, I trust, which is "I believe" or "I put my trust". The word financing which means trust, which means the bank trusts someone to carry out the mandate given by the bank as shahibul mall. The funds must be used properly, fairly and must be equipped with clear and mutually beneficial ties and conditions for both parties, the commandment of the word of Allah in: Surah An-Nisa '(4) verse 29: "O you who believe Do not take the wealth of your neighbor in an immoral way, except by way of commerce which is consensual among you. And don't kill yourself, actually Allah is Most Merciful to you. "